Patterns of adolescent students' use of mobile phones for educational activities - H. M. Samitha Herath; W. M. Shaminda Wanasinghe (Eureka: Journal of Educational Research, 2024)
This study was conducted to identify patterns of adolescent students' use of mobile phones for educational activities. Survey research design was used and implemented through three objectives, determining the extent of mobile phone use among adolescent students, identifying the mobile phone usage patterns of adolescent school students, and identifying the problems faced by the students due to the use of mobile phones. The sample is eighty grade 12 students studying advanced level technology stream in two schools of Ibbagamuwa education division. Using questionnaire and interview schedule collected data. Both quantitative and qualitative data analysis techniques used. According to the data analysis, Mobile phone usage among adolescent students has increased rapidly in the year 2020 and all students are currently using mobile phones and weaning them from using mobile phones is an impossible task, and get them to use mobile phones effectively is possible. They often try to keep and use their mobile phone privately. Also use it for non-academic activities. The use of mobile phones has weakened their relationships. The main reasons for uncontrolled use of mobile phones by students are parents' lax policies and lack of knowledge. Following suggestions are made to guide adolescent students to use mobile phones effectively. Implementation of training programs for students and teachers on use of mobile phones for academic purposes and awareness programs for parents. Students should directed to use smart classrooms and tab computers in a planned schedule in school. Apply for concessional data packages and scholarships for students.